Seamless fault-tolerant operation of a modular multilevel converter with switch open-circuit fault diagnosis in a distributed control architecture - Yang, Shunfeng (2019)
Modularity and high reliability from redundancy are the two attractive advantages of modular multilevel converters (MMCs). This paper elaborates a switch open-circuit fault diagnosis and a fault-tolerant operation scheme for MMCs with distributed control. The proposed fault diagnosis and fault-tolerant control method can significantly improve the reliability of the MMC while maintaining the modularity of its software implementation. By distributing fault diagnosis into submodules, its local controller is capable of identifying the switching devices in open-circuit fault without extra hardware circuitry. Based on the real-time measurements of submodule terminal voltage and arm current, single, or multiple faulty switches can be identified within 3.5 ms without triggering faulty alarms. Furthermore, a new fault-tolerant operation is proposed to maintain the output current, internal dynamics, and switching harmonics unchanged after the faulty submodule is bypassed. This is achieved by resetting the period and phase registers in the local controller according to the information of bypassed submodules. The control loops of the MMC are not influenced by the proposed fault diagnosis and fault-tolerant operation, making the operation transition seamless and reliable. Experimental results show that fault identification and system reconfiguration can be completed within 5 ms, and the MMC can seamlessly and smooth ride through the switch open-circuit faults without severe malfunction and catastrophic damages.